Evolving environmental awareness and shifts in management priorities: a socioeconomic lens on the min river basin, China - Zeng, Daile; Chen, Boya; Wang, Jingxin; Innes, John L.; Lu, Juliet; Guo, Futao; Yan, Yancun; Wang, Guangyu (Frontiers in Environmental Science, 2023)
Watersheds have experienced economic and demographic development for decades. In China, this development has been associated with environmental degradation, including water quality deterioration, abnormal stream flow, and biotic resource depletion. Effective watershed management incorporates sustainability and public involvement, enabling the long-term security of the human and nature worlds. Management strategies however need to take into account local conditions, as every watershed is unique. This paper adopts the analytic hierarchy process (AHP) combined with the random forest model to investigate the shift in participants' environmental awareness across different socioeconomic groups over the past 15 years. Additionally, it scrutinizes the changing public perceptions on the management priorities and areas requiring enhancement. The AHP index highlighted the importance of environmental behavioral intentions (EBI) as a component of environmental awareness (EA). Between 2006 and 2021, significant changes occurred in public environmental awareness (perception, knowledge, behavioral intention) and perceived management priorities, stressing the need for timely adjustment of management policies. Notably, environmental concern (EC) appears to have decreased over time, reflecting effective management and increased governmental attention. Emphasis on the recreational ecosystem services offered by watershed forests has increased. Males, individuals aged over 40-years-old, and individuals located in the upper reach possessed higher risk perceptions than other groups. These findings may help policymakers to adjust management priorities based on geographic region and may assist them in promoting more effective measures to communicate watershed sustainable management goals and strategies to the public.